Effects of Three Foodborne Polyphenols on the Physicochemical Properties of Potato Starch - Tiange CHEN; Yongxian LI; Lu WANG; Min XU; Lixin HUANG; Lei LIU (Shipin gongye ke-ji)
Potatoes are a type of grain and vegetable crop that contain polyphenols and starch. The interaction between polyphenols and starch occurs during the processing of potatoes. This research was designed to investigate the effects of different foodborne polyphenols on the physicochemical and functional properties of potato starch (PS). Changes in the solubility, swelling, retrogradation, freeze-thaw stability, pasting properties, thermal, and rheological properties of potato starch were analyzed after the addition of varying concentrations (5%, 10%, 15%, 20%) of ferulic acid (FA), gallic acid (GA), and rutin (RT). The results demonstrated that ferulic acid and gallic acid significantly increased the solubility and decreased the swelling compared to the native starch (P<0.05). The addition of 20% ferulic acid and gallic acid resulted in a 1.3-fold and 1.8-fold increase in the solubility of potato starch, respectively. All three polyphenols could significantly reduce the retrogradation, water precipitation rate, and peak viscosity of potato starch (P<0.05). Thermodynamic analysis revealed that ferulic acid and gallic acid exerted a significant influence on lowering both the pasting temperature and peak temperature of potato starch (P<0.05), while no significant influence of rutin was observed. The rheological characteristics of potato starch paste in a steady-state condition indicated that the polyphenol-starch paste exhibited notable shear-thinning behavior and functioned as a pseudoplastic fluid. These findings provide a theoretical reference for the processing of potato starch-based foods.